2016
DOI: 10.1007/s40846-016-0184-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Kinect 3D Sensor for Healthcare Imaging

Abstract: Microsoft Kinect is a three-dimensional (3D) sensor originally designed for gaming that has received growing interest as a cost-effective and safe device for healthcare imaging. Recent applications of Kinect in health monitoring, screening, rehabilitation, assistance systems, and intervention support are reviewed here. The suitability of available technologies for healthcare imaging applications is assessed. The performance of Kinect I, based on structured light technology, is compared with that of the more re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 58 publications
1
41
0
Order By: Relevance
“…However, even within that range of standard deviations, the uncertainty of defocus is only on the order of centimetres. Furthermore, in accordance with the already published literature, it can be concluded that the device is feasible and sufficiently reliable for biomedical applications [18][19][20].…”
Section: Reliability Of the Depth Estimationssupporting
confidence: 86%
See 1 more Smart Citation
“…However, even within that range of standard deviations, the uncertainty of defocus is only on the order of centimetres. Furthermore, in accordance with the already published literature, it can be concluded that the device is feasible and sufficiently reliable for biomedical applications [18][19][20].…”
Section: Reliability Of the Depth Estimationssupporting
confidence: 86%
“…1). The reliability of the Kinect camera with respect to depth measurements has been confirmed before [18][19][20].…”
Section: Equipmentmentioning
confidence: 79%
“…However, these devices presently work with a borderline level of acceptance of depth resolution. Many research works investigated the performance of RGB-D cameras such as Kinect v1 sensor (Khoshelham and Elberink, 2012;Mallick et al, 2014), Kinect v2 sensor (Lachat et al, 2015;Pöhlmann et al, 2016;Sarbolandi et al, 2015) and Intel RealSense RGB-D imaging systems (Keselman et al, 2017). The Kinect v2 sensor has been markedly used in many research works due its promising properties.…”
Section: Camera System and Sensing Propertiesmentioning
confidence: 99%
“…It offers a wide field of view (70 × 60 degrees) and recognition up to 4.5 m from the device [12]. Several studies have demonstrated that spatiotemporal parameters can be validly obtained by Microsoft Kinect V2 [13,14]. The set-up of the interface between the Microsoft Kinect V2 and the Unity3D engine is effortless because the manufacturer provides a Software Development Kit (SDK) and a Unity add-on, which gives developers access to body joint positions and orientations that can be used directly in rehabilitation game development.…”
Section: Descriptionmentioning
confidence: 99%